Too many men, too short lives: The effect of the male-biased sex ratio on mortality - Chang, Simon; Kan, Kamhon; Zhang, Xiaobo (Institute of Labor Economics, 2020)
Using a natural experiment in Taiwan, this paper shows that exposure to male-biased sex ratios at the marriageable ages is associated with a greater likelihood of death in later life. Half a million soldiers from Mainland China who retreated to Taiwan after a civil war in the late 1940s were subject to a marriage ban. When the ban was lifted in 1959, the great influx of the soldiers into the marriage market suddenly tipped the balance in favor of women. We have found that men subject to this massive marriage market squeeze exhibited higher mortality rates at age 50–64. Surprisingly, the deadly effect, albeit of a much smaller magnitude, is also found among women. We show that this is likely driven by the widowhood effect—women's mortality rate increased after their husbands' deaths.